2013
DOI: 10.1007/s10897-013-9629-8
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin Use is Associated with Lower Prostate Cancer Risk in Male Carriers of BRCA Mutations

Abstract: Previous studies have shown that male BRCA mutation carriers stand at increased risk of developing prostate cancer and have concerns about developing cancer. Genetic counseling practitioners often discuss strategies for reducing the risk of cancer for patients at high risk due to their genetic background. Addressing modifiable health habits is one such strategy. Unfortunately, modifiable risk factors for prostate cancer have only been documented in the general population and have not yet been studied in the BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Among the 53 included studies, 16 were cohort studies (2 563 519 participants), 33 were case-control studies (44 536 participants), and 4 were cross-sectional studies (12 098 221 participants) . Although most studies were population- or registry-based analyses, several articles presented single- or multiple-institution analyses (Table).…”
Section: Results and Evidence Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 53 included studies, 16 were cohort studies (2 563 519 participants), 33 were case-control studies (44 536 participants), and 4 were cross-sectional studies (12 098 221 participants) . Although most studies were population- or registry-based analyses, several articles presented single- or multiple-institution analyses (Table).…”
Section: Results and Evidence Synthesismentioning
confidence: 99%
“…[16][17][18][19]32,33,37,38 Most case-control studies (26 [79%]) were considered to have a moderate to high risk of bias. 8,9,39,40,42,43,[45][46][47][48]51,52,[54][55][56][58][59][60][61][62][63][64][65][66][67][68] Although cases were typically well defined, the use of hospital-based instead of community-based controls was considered a potential source of bias among many case-control studies. Ascertainment of exposure was also a common source of bias among casecontrol studies.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
“…In yet another study involving 47,882 patients, aspirin usage was not found to reduce total PCA incidence, but potentially reduced the occurrence of metastatic disease [82]. This may be related to the findings of another study of 74 men from families with the BRCA mutation where it was found that daily aspirin use conferred some protection against PCA [83]. Another study of 29,450 men also found PCA protective benefits of daily aspirin usage [84].…”
Section: Prostate Cancer Chemopreventive Agentsmentioning
confidence: 99%
“…Chronic inflammation associated with diseases like Rheumatoid Arthritis, Crohns disease, Chronic obstructive pulmonary disease (COPD) and pancreatitis is known to increase cancer risk [4], [5] and neutrophil depletion has been shown to reduce tumor burden in a mouse model of lung cancer [6]. The connection between inflammation and cancer risk is further supported by studies that suggest that treatment with anti-inflammatory agents can decrease the incidence of some cancers [7][9]. Although chronic inflammation has been linked to EMT and cancer invasion [10][12], it is not clear how innate immune inflammation is associated with EMT and participates in cancer progression.…”
Section: Introductionmentioning
confidence: 99%